i forgot to divide the the whole thing by three. so my final answer, which is also wrong according to my book, is
-4(4x-1)^1/2(x-1)
the answer in the book is 4(4x-1)^1/2(x-1).
What's tripping me up is why mine starts with -4. I must be doing something wrong when simplifying [1-1/3(4x-1)]
where i did 1 - 1/3(4x) + 1/3(1)=
1 - 4x/3 + 1/3 =
3/3 - 4x/3 + 1/3 =
-4x/3 - (3/3 + 1/3) =
(-4x - 4)/3 =
-4(x-1)/3
Look very carefully at the original problem to make sure you've copied correctly. Is this the expression that you were given?
And is this the exact answer that is written in the book?
If so, your book is in error. The correct answer would be
or, in radical form,